High-Performance Work Practices and Employee Wellbeing—Does Health-Oriented Leadership Make a Difference? - Hauff, Sven; Krick, Annika; Klebe, Laura; Felfe, Jörg (Frontiers in Psychology, 2022)
This paper sheds further light on the contextual boundaries in the relationship between high-performance work practices and employee well-being. In particular, we analyze whether this relationship is moderated by health-oriented leadership behavior, which describes the extent to which leaders value, are aware of and protect their followers’ health at work. Our analyses are based on employee data (N = 1345) from Germany, covering two points in time. Findings show positive associations between HPWPs and happiness-related (i.e., engagement, commitment) and health-related (i.e., general health, physical health complaints, mental health complaints, strain) well-being outcomes. The positive relationship between HPWPs and employee well-being is weaker the more employees experience leadership behavior in terms of staff care. Thus, our results provide further for a substitutive or compensatory effect between HRM and leadership.